Optimized Birch Bark Extract-Loaded Colloidal Dispersion Using Hydrogenated Phospholipids as Stabilizer - Francis Kamau Mwiiri; Rolf Daniels (MDPI AG, 2020)
This study investigated the formulation and processing of aqueous colloidal dispersions containing a birch bark dry extract (TE) as the active substance and hydrogenated phospholipids (Phospholipon 90H) as stabilizer, which can be used in the preparation of electrospun wound dressings. Colloidal dispersions manufactured using a two-stage homogenization process had a bimodal particle size distribution, which was most significantly (p < 0.0001) affected by the phospholipid content. The size of the single particles decreased from an average particle size of about 4 µm to a particle size of approximately 400 nm. Dynamic interfacial tension studies performed using a profile analysis tensiometer (PAT) showed that the phospholipids strongly declined the interfacial tension, whereas a further decrease was observed when phospholipids were combined with birch bark extract. Interfacial viscoelasticity properties analyzed using the oscillating drop technique resulted in an increase of both interfacial elasticity and viscosity values. These results indicated that the phospholipids are preferentially located at the lipophilic/water interface and a stable film is formed. Furthermore, the results point to a synergistic interaction between phospholipids and TE. Confocal Raman microscopy (CRM) suggested that the TE is predominantly located in the oil phase and the phospholipids at the interface.